Estimating Cue Strengths in Oral Production in a Japanese Learner Corpus - Tanaka, Nozomi (Frontiers in Communication, 2022)
Word order, case marking, and animacy are cues used to convey and comprehend argument roles in transitive events. Japanese, however, is characterized by flexible word order, null arguments, and case-marker omission. This study analyzes corpus data of interviews between native Japanese speakers and L1-English and L1-Korean learners to examine these characteristics in both input to learners and learners’ own production. The relative importance of the three cues is estimated based on their distributional properties using the competition model framework. The findings indicate that animacy was the strongest cue for the native speakers and, when at least one NP was elided, for the learners. However, when both subject and object were present, learners adhered to SOV word order. Case marking was reliable when present but was so frequently omitted that it was not a useful cue, contra previous reports. L1 and proficiency effects are also discussed.